Geologic controls on reservoir quality of the Hunton and Viola limestones in the Leach Field, Jackson County, Kansas - Rennaker, Joshua Jay (Kansas State University, 2016)
The area of study for this project is the Leach Field, which is located in Jackson County, Kansas. Production in the Leach Field has historically been disappointing, with 388,787 barrels of oil being produced since the field’s discovery in 1963 (KGS, 2015). Production of the field has been highly variable, with only 20,568 barrels of oil being produced in the last 20 years. Economic and other concerns that have impacted production and production rates of the field include: low oil prices soon after its discovery, numerous changes of ownership, and lack of significant production infrastructure in the area. Stroke of Luck Energy & Exploration, LLC. has recently purchased the majority of the leases and wells in the Leach Field, and is reestablishing the field as a productive oil field. Plans include: washing down several plugged and abandoned wells, and drill new wells to increase production in the field. The goal of this study was to determine the major geologic factors controlling reservoir quality in the Hunton and Viola Limestone Formations in the Leach Field, so that a future exploration model can be developed to help increase and stabilize the field's overall production. This model was created by applying several testing methods including: well logging analysis, microscope analysis, and subsurface mapping. Based on these results it was determined that the quality of the reservoir rocks is controlled by the degree of dolomitizaiton in both formations. Reservoir quality is as important as structure in determining well productivity in the Leach Field.
Keywords: Geologic Controls; Reservoir Quality; Leach Field